Reflections on the emotional development of the mother, on the basis of Winnicott´s theory - Torres-Vilar, Natalia (2006)
This paper offers some insights into the experiences of mothers in their initial bonding with their children. To this end, the author offers a discussion of Winnicott’s view of the emotional development of the baby, emphasizing the process from the first drafts of the ego to the possibility of the creative act. This discussion is enriched by the addition of the other component of the bond: the mother. It is suggested that, in normal cases, together with the emotional development of the baby and through the phenomena of empathy and crossidentification, a reinforcement of the emotional development of the mother takes place.